2002
DOI: 10.2320/matertrans.43.1605
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-pressure Annealing Process to Dual Damascene Copper Interconnections

Abstract: We have carried out a detailed study of the relevant process techniques by using high-pressure annealing in order to embed Cu interconnections flawlessly into via holes or trenches, and have thereby identified a process technique increase the reliability of electrical circuits. In the present study, Cu interconnections were subjected to heat treatment in a high-pressure argon gas atmosphere (150 MPa) with the prospect that such a process might lead to optimized conditions for creating the embedded Cu interconn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The PVD method is attractive from the viewpoint of simplifying the entire process and alloying of Cu-film to further enhance the electron migration resistance for example. However the PVDCu films requires higher temperatures than the ECD films to fill via holes completely by the high pressure annealing process [1,2]. On the other hand, it was found that the addition of Sb to the PVD-Cu lowers the required temperature.…”
mentioning
confidence: 99%
“…The PVD method is attractive from the viewpoint of simplifying the entire process and alloying of Cu-film to further enhance the electron migration resistance for example. However the PVDCu films requires higher temperatures than the ECD films to fill via holes completely by the high pressure annealing process [1,2]. On the other hand, it was found that the addition of Sb to the PVD-Cu lowers the required temperature.…”
mentioning
confidence: 99%
“…Figure 1 shows a schematic drawing of the high-pressure annealing system used in this study. 13 In the experiments, the temperature and pressure were increased linearly from room temperature (RT) with no applied load up to a fixed temperature (up to 600°C) and pressure (150 MPa) at a heating rate of 5°C min À1 . The high temperature and pressure were maintained for 120 min, and then decreased linearly back to RT with no applied load at a cooling rate of 5°C min À1 .…”
Section: Methodsmentioning
confidence: 99%
“…In this process, Cu is deposited into vias and trenches by sputtering and is then mechanically deformed and embedded in the vias and trenches by high-temperature high-pressure treatment, thereby increasing the reliability of the interconnect and consequently improving yield. [12][13][14] Sputtered Cu films have higher purity compared with electroplated ones, and there is no possibility of inclusion of electrochemical reagents. This fact has encouraged us to reconsider the application of sputtering in the fabrication of Cu interconnections, because even for electroplated Cu films, it is still necessary to sputter the seed layers which act as electrodes for electroplating.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows a cross-sectional sketch of the pressure vessel that was used for the high-pressure annealing process in this study. 13 After the high-pressure annealing process, parts of the TEGs were examined by cross-sectional secondary-ion microscopy (SIM) so that we could estimate the filling level of the Cu. The filling level of the Cu was determined quantitatively as the filling area ratio by editing of the SIM images.…”
Section: Methodsmentioning
confidence: 99%
“…In this process Cu interconnections are deposited onto via holes and trenches by a sputtering method and are then mechanically deformed and embedded into via holes and trenches by high-temperature and high-pressure treatments, thereby increasing the reliability of the Cu interconnections and consequently improving yields. [9][10][11][12][13][14] However, the embedding mechanism for Cu interconnections has not yet been elucidated sufficiently. In this study we analyzed the reflow phenomenon of Cu interconnection into via holes by the use of viscoelastic deformation simulation, and we considered the mechanics of the reflow mechanism.…”
Section: Introductionmentioning
confidence: 99%